Study guides

☆☆

Q: What is y + 2 = 4(x + 2) in standard form?

Write your answer...

Submit

Related questions

y=4x*2y=8x

If you mean: y = -4x-1 then it is 4x+y+1 = 0 in standard form

If the equation is y = 4x + 8, then the standard form is 4x - y + 8 = 0

4x-y+7=0

y=-x^2+4x-3

8x-3y=6-4x gives 12x-3y=6 which in standard form is y=-2+4x

-3

-3

22

8 + y = 4x8 + y - 4x = 4x - 4x 8 + y - 4x = 0 8 - 4x + y = 0

4x - y^2 is in its simplest form. (4x - y)^2 factors to (4x - y)(4x - y)

4x + y = 10 is a perfectly valid functional form. The standard form is 4x + y - 10 = 0

If you mean y = -x+3 then it is x+y-3 = 0 in standard form

-3

-3

Standard form is in the form of Ax+By=C . A must be positive, not a fraction. So, this one is 4x-y=-7 because the coefficient of x has to be changed.

4x - 5y = -2 so 5y = 4x + 2 or y = 4/5x + 2/5 Now that it is in the standard form, the slope is the coefficint of x ie 4/5.

x² + y² - 4x + y - 1 = 0 ( x² - 4x ) + ( y² + y ) = 1 ( x² - 4x + 4 ) + [ y² + y + (1/4) ] = 1 + 4 + (1/4) ( x - 2 )² + [ y + (1/2) ]² = [ √(21) / 2 ]² This equation represents a Circle with Centre ≡ ( 2, -1/2 ) and Radius = √(21) / 2. ________________________________________ Happy To Help ! ________________________________________

4x - 5y = 0 standard form of slope intercept line equation is y = mx + c m = slop and c = intercept rewrite the 4x - 5y = 0 in standard form y = 4/3 x compare it with standard form, and slope = 4/5

y=4x+2

3y - 4x = 24 The first step is to write it in the standard form (y=mx + c) 3y = 4x + 24 y = (4x + 24)/3 y = 4x/3 + 8 The y-intercept is 8 and the slope/gradient is 4/3

Slope intercept form looks like y=mx+b, so we want to get y on on side by itself. -4x+2y=2 Add 4x to both sides: 2y=2+4x Divide both sides by 2: y=1+2x or y=2x+1

3+4x=2y-9 Convert to standard form: 2y = 4x+12 or y = 2x+6 The slope, then, is the coefficient of x ie 2.

Put in slope intercept form and read it off the equation. 4X - 9Y = 18 - 9Y = - 4X + 18 Y = (4/9)X - 2 =========== 2 is the Y intercept.

The vertex form: y = a(x - h)2 + k where (h, k) is the vertex. y = x2 + 4x + 7 add and subtract 4 to the right side to complete the square y = x2 + 4x + 4 - 4 + 7 form the square y = (x + 2)2 + 3 write + 2 = -(-2) y = [x - (-2)]2 + 3 Thus, the vertex is (-2, 3)